1985
DOI: 10.1002/jmor.1051840307
|View full text |Cite
|
Sign up to set email alerts
|

Functional organization of battery cell complexes in tentacles of Hydra attenuata

Abstract: Ultrastructural and light microscopic observations on the organization of thick and thin regions of hydra's tentacles, made on serial sections and on whole fixed, plastic-embedded tentacles, reveal the existence of two levels of anatomical order in the tentacle ectoderm: (1) The battery-cell complex (BCC), composed of a single epitheliomuscular cell (EMC) and its content of enclosed nematocytes and neurons; and (2) the battery cell complex ring (BCC ring), an arrangement of 4 or more BCCs into larger units org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 39 publications
(1 reference statement)
1
37
0
Order By: Relevance
“…This neurosensory ectoderm thus functionally corresponds to a ganglion-associated sensory organ of a higher animal. A comparable situation has been reported for the subunits of the tentacles of Hydra, the battery cell complexes (Hufnagel et al, 1985;Kass-Simon and Hufnagel, 1992).…”
supporting
confidence: 55%
“…This neurosensory ectoderm thus functionally corresponds to a ganglion-associated sensory organ of a higher animal. A comparable situation has been reported for the subunits of the tentacles of Hydra, the battery cell complexes (Hufnagel et al, 1985;Kass-Simon and Hufnagel, 1992).…”
supporting
confidence: 55%
“…A remarkable feature of the net is, in fact, its plasticity: neurons are continually migrating to be eliminated at the apical and basal ends of the polyp together with the adjacent epithelia (Dunne et al, 1985;Bode et al, 1986), thus implying that extensive synapse remodeling must occur in physiological conditions. Furthermore, though Hydra polyps have no recognizable organs, a detailed ultrastructural analysis of the epithelial cells of the tentacles, the battery cells, showed that these cells enclose in their cytoplasm sensory and ganglion neurons as well as myonemes and different types of nematocytes, anchored by gap and septate junctions respectively (Hufnagel et al, 1985). The authors suggest that these cell complexes may represent the functional units by which tentacles exert their functions: sensory perception, bending and contraction, prey capture (Hufnagel and Kass-Simon, 1988).…”
Section: The Nervous Net Of Hydra: Anatomy Ultrastructure and Physiomentioning
confidence: 99%
“…This interpretation is supported by the conspicuous size of the ciliary rootlet, which resembles that of the stretchsensitive chordotonal receptor cells of insects (e.g., Wolfrum, 1991). A similar arrangement of a recessed, interconnected cilium combined with a strong ciliary rootlet was found in the "sensory-motor interneuron" of Hydra (Westfall, 1973;Kinnamon and Westfall, 1982;Hufnagel et al, 1985). It was supposed to transduce stretching of the tentacle in the direction of the cilium, in analogy to the function of insect chordotonal receptors (Golz and Thurm, 1991b; see also Peteya, 1973).…”
Section: Sensory Featuresmentioning
confidence: 95%
“…Their neural structures are evolutionarily the oldest neural elements accessible today. Tentacles that are organized uniformly over their length have been investigated in many studies, like those of the freshwater hydrozoan Hydra (for ultrastucture, see Slautterback, 1967;Westfall, 1973;Westfall and Kinnamon, 1978;Hufnagel et al, 1985) and of Anthozoa (Westfall, 1965;Watson and Hessinger, 1989;Westfall and Sayyar, 1997). In the hydrozoan order Capitata, in contrast, sensory and effector structures are concentrated in terminal spheres at the tips of the tentacles (capitate tentacles).…”
mentioning
confidence: 97%